Gastrointestinal involvement in patients with vasculitis: IgA vasculitis and eosinophilic granulomatosis with polyangiitis - Kawasaki, Keisuke; Nakamura, Shotaro; Esaki, Motohiro; Kurahara, Koichi; Eizuka, Makoto; Okamoto, Yasuharu; Hirata, Takashi; Hirahashi, Minako; Oshiro, Yumi; Yanai, Shunichi; Sato, Kunihiko; Toya, Yosuke; Maemondo, Makoto; Terayama, Yasuo; Sugai, Tamotsu; Matsumoto, Takayuki (Endoscopy International Open, 2019)
Background and study aims Among vasculitides, IgA vasculitis (IgAV) and eosinophilic granulomatosis with polyangiitis (EGPA) frequently damage the gastrointestinal tract. However, only a few studies have investigated the entire gastrointestinal tract in patients with IgAV or EGPA by endoscopy. The aim of this study was to clarify endoscopic characteristics of patients with IgAV and those with EGPA. Patients and methods Clinicopathological and endoscopic findings were retrospectively compared between 33 patients with IgAV and 19 patients with EGPA. Results Gastrointestinal involvement was observed in 33 patients with IgAV (100 %) and in 8 patients with EPGA (42 %; P = 0.0001). Duodenal involvement was more frequent in patients with IgAV (75.8 %) than in those with EGPA (21.1 %, P = 0.0002). Jejunoileal involvement was frequent in both groups (IgAV 94.4 %; EGPA 77.8 %). Gastric mucosal erythema was more frequent in patients with IgAV (18.2 %) than in those with EGPA (0 %, P = 0.0481). Duodenal mucosal erythema (IgAV 54.6 %; EGPA 21.1 %, P = 0.0227), ulcer (IgAV 33.3 %; EGPA 0 %, P = 0.0041), and hematoma-like protrusion (IgAV 21.1 %; EGPA 0 %, P = 0.039) were more frequently observed in patients with IgAV than in those with EGPA. Conclusions Frequent duodenal involvement, gastric mucosal erythema, and duodenal lesions including erythema, ulcer, and hematoma-like protrusion are characteristic of patients with IgAV. Because jejunoileal involvement was frequent in both groups of patients, small-bowel endoscopies should be performed for diagnosis of small-bowel lesions in patients with IgAV and EGPA.